Empirical formulae for dispersion and effective mode area in hollow-core antiresonant fibers - Hasan, Md. Imran (2020)
We present empirical formulae that provide dispersion and effective area of the fundamental mode in hollow-core antiresonant fibers. The formulae draw on the structural parameters of the fiber and allow one to obtain the guiding properties over a wide spectral bandwidth, without the need for time consuming numerical simulations. The formulae are validated by comparing their results with those obtained using the finite-element method. We also analyze the effects of changing the number of antiresonant tubes, as well as adding nested elements in the antiresonant tubes on the guiding properties.